Histopathological Spectrum of Gastrointestinal Polyps: A Retrospective Study at a Tertiary Care Hospital - Sahu, Ruby; Singh, Shashikant; Ahuja, Arvind (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: Gastrointestinal polypoidal lesions are commonly encountered lesions on endoscopic examination. The histopathological examination categorises these lesions into neoplastic and non-neoplastic since these have the potential to get transformed into malignancy. This study aimed to assess the clinical profile as well as the histopathological spectrum of gastrointestinal polyps observed during endoscopic evaluation.Methods: This study was a retrospective cross-sectional observational study conducted in the department of pathology at a tertiary care centre. All the histologically diagnosed gastrointestinal polypoidal lesions over a period of eight years were retrieved from the archives. Immunohistochemistry was applied as and when necessary. Univariate analysis was performed. Categorical variables were presented in number and percentage (%), and continuous variables were presented as mean. Appropriate descriptive statistics and graphical displays for different types of data have been presented. Result: Two hundred cases of gastrointestinal tract polypoidal lesions were included. The age of the patients ranged from 8 months to 90 years. Juvenile rectal polyp was the most frequently encountered non-neoplastic lesion constituting 42.5 %( 85/200) and conventional adenoma was the commonest neoplastic lesion constituting 17.5 %(35/200) of cases. Most of the polypoidal lesions were less than 1 cm; however, in 6.5 %( 13/200) cases, it was larger than 1cm in size.Conclusion: The gastrointestinal tract had a diverse range of non-neoplastic and neoplastic polyps. Histopathology is important in obtaining at a final diagnosis since it allows for a detailed investigation of occurrences and aids in distinguishing non-neoplastic disorders from those with clinical manifestations of malignancy. Keywords: Gastrointestinal polyps, hyperplastic polyp, conventional adenoma